(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2024)
This manuscript presents a reflection and analysis on the pedagogical interactions experienced in the educational field during the COVID-19 pandemic. The methodology implemented was qualitative, aiming to account for the subjectivities and intersubjectivities of the interviewees (Krause, 1995). The information collection technique involved in-depth interviews and secondary data review (Valles, 1999). There were 6 female interviewees, 2 teachers, and 2 students, aged between 20 and 69, from the Metropolitan Region and the V Region. The data analysis technique was discourse analysis by Ruiz (2009), aligning with the objectives of the study. Based on the results and their analysis, it was possible to develop a methodological proposal with pedagogical guidelines aimed at fostering healthy, affective, diverse, and inclusive pedagogical interactions in an emergency education context as described. Thus, educators are called upon to adopt transformative pedagogical practices conducive to democratic and equitable relationships, in pursuit of greater social justice.